Mental Health in the Qur'an Perspective and Its Relevance with Contemporary Islamic Education in Indonesia - Ali; Mu'iz, Abdul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study aims to accomplish the following objectives: to analyze the concept of mental health from the perspective of the Quran, to examine the concept of contemporary Islamic education in Indonesia, and to assess the relevance of Quranic perspectives on mental health within the context of contemporary Islamic education in Indonesia. To achieve these objectives, a qualitative approach was employed in this study. This approach emphasizes the utilization of deductive and inductive inference processes and the analysis of the dynamic interplay among observed phenomena. The study yielded descriptive data that sheds light on the Quranic theory of mental health and its applicability to contemporary Islamic education in Indonesia. The findings of this study suggest that contemporary Islamic education in Indonesia holds the potential to enhance the quality of human mentality. This enhancement can be achieved through virtuous actions such as prayer, dhikr (remembrance of God), fasting, zakat (charity), pilgrimage, and ruqyah (spiritual healing). Furthermore, the evaluation process should incorporate moral dimensions. In summary, this research demonstrates that contemporary Islamic education in Indonesia can contribute to the promotion of good mental health among individuals.